Individual rights in Robert Nozick’s political philosophy - Saar, Marcin (Hybris, 2020)
With respect to Robert Nozick’s political philosophy (as it is to be found in Anarchy, State, and Utopia), one of the most prominent theses is the one that asserts that in Nozick’s mind individual rights are founded on the principle of self-ownership - the principle that says that all individuals have, with regard to themselves, rights identical with (or parallel to) rights of property. In this paper we want to focus on slightly different interpretation of Nozick’s thought. First, we summarize Nozick’s account of rights: its main points being the individual being proper subject of rights and the nature of rights as side-constraints. Then we turn our attention to the metnioned interpretation itself. It was proposed by Mark D. Friedman, and it synthesizes Nozick’s insights on this topic scattered throughout his book. It focuses on argument “from moral form to moral content” (from the fact that the form of morality includes side-constraints to the content of libertarian constraint against aggression) suggested by Nozick and on features in virtue of which persons have rights - this features being free will, rationality, moral agency and ability to live one’s life according to some general conception of it.